Unsteady Turbulent Flow Modelling and Applications - Roos Launchbury, David; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2016)
The master thesis of David Roos Launchbury deals with the implementation and validation of a numerical solver for incompressible large eddy simulation (LES) with heat transfer in OpenFOAM. Academic and industrial cases, ranging from flow between parallel plates to film cooling, are investigated utilising existing and newly-implemented turbulence models. Simulations using no turbulence models, i.e. under-resolved DNS (UDNS) simulations, are performed for comparison. Very good results are obtained in all cases with variations among the individual models, with the UDNS simulations performing surprisingly well. The study shows that the developed software is able to simulate complex cases reliably and accurately. Contents Large Eddy Simulation Subgrid Models Solver Validation Parallel Performance Recommendations for LES Simulations  Target Groups Lecturers and Students of Engineering and Fluid Dynamics Readers interested in Computational Fluid Dynamics and Turbulence Modelling The Author David Roos Launchbury finished his Master's Degree in Mechanical Engineering in Horw, Switzerland, and is currently working as research associate at Lucerne University of Applied Sciences and Arts - Engineering and Architecture.
Large Eddy Simulation -- Subgrid Models -- Solver -- Validation -- Parallel Performance -- Recommendations for LES Simulations.  .
Keywords: Engineering mathematics; Engineering -- Data processing; Computer simulation; Mechanical engineering; Mathematical and Computational Engineering Applications; Computer Modelling; Mechanical Engineering